Composition and phosphorylation-dependent functional interactions of thylakoid protein complexes in Arabidopsis - Rantala, Marjaana (fi=Turun yliopisto|en=University of Turku|, 2018)
In higher plants the thylakoid embedded pigment-protein complexes, photosystem (PS) I and PSII together with their respective light harvesting complex (LHC) antennas work in series to harvest solar energy and convert it into chemical energy. Profound understanding of the composition and interactions of the photosynthetic machinery is a prerequisite for understanding the function and regulation of the energy conversion reactions. The structure of individual components of the photosynthetic machinery has been resolved in high resolution and currently the interest is targeted at the supramolecular organization and light-dependent regulation of the photosynthetic protein complexes. This thesis elucidates the overall organization of the thylakoid protein complex network providing structural insights into the hierarchical protein complex interactions in Arabidopsis thaliana. LHCII trimers are shown to mediate the supramolecular assemblies of the two photosystems and the strength of the interactions between individual subcomplexes is demonstrated using an optimized protein complex solubilization system together with two-dimensional native gel electrophoresis. This thesis further addresses the dynamic nature of the protein super- and megacomplexes upon short-term light acclimation. It is shown that light intensity dependent LHCII phosphorylation causes re-arrangements of the protein complexes particularly in the non-appressed regions of the thylakoid membrane. The differential phosphorylation of distinct LHCII proteins, Lhcb1 and Lhcb2, is shown to occur in different pools of LHCII antenna trimers. Lhcb1 was found phosphorylated mainly in PSII-LHCII supercomplexes, whereas phosphorylated Lhcb2 is located exclusively in loosely bound LHCII, which is known to have a role in mediating the interaction of the PSI and PSII complexes upon dynamic changes in light intensity. The results of my thesis provide valuable information regarding the toolbox needed for the enhancement of photosynthetic productivity in the global attempts to meet the future challenges in food and bioenergy production.